A system for testing of membranes and catalysts - Lindmark, Jonas (2003)
This project was started to speed up the evaluation of catalytic samples prepared at the division of Chemical Technology, Luleå University of Technology (LTU). Samples had previously been sent to University of Cape Town (UCT) for testing but there was a need for a reactor system in Luleå to make the catalysis research more efficient. A reactor system was constructed consisting of a few main components. The system can be used to carry out many types of studies in the fields of reaction engineering and catalysis. The system will mainly be controlled by a computer system although there will be some manual valves. The system consists of three main parts: a pair of saturators, a reactor inside a furnace and a gas chromatograph. The gas chromatograph is used to analyse the products from the reactor. The components were purchased separately from different suppliers and was mounted together in a laboratory in Luleå. The reactor system was tested successfully. Validerat; 20101217 (root)